Numerical simulation of waste landfill biodegradation: Fitting experimental data - Vladimir Buelvas-Hernandez; Juliana Lucía Moreno-Medina; Marcela Mercado-Montoya (Dyna)
Landfill remains economically viable for the disposal of Municipal Solid Waste (MSW), however, experiences of failure in several Colombian and global locations, lead to soil, water, and air pollution, harming ecosystems, and biodiversity. Numerical models can help improve the design by considering biodegradation, hydraulic, thermal, and mechanical phenomena involved in landfills. This paper presents a simulation of the landfill biodegradation, calibrating parameters to make results match experimental data from previous references. COMSOL Multiphysics was used to implement McDougall's biodegradation model, tracking organic matter transformation into volatile fatty acids (VFA) and methane (CH4) production via acetogenesis. Parameters taken from previous references were recalibrated to fit data from six US landfills. The results for the concentration variation with time for organic matter, VFA and CH4 successfully follows the expected behavior and fits the experimental data. McDougall's 2007 model, successfully implemented in COMSOL, can be calibrated for data from Colombian and global landfills.